Epidermoid cyst within an intrapancreatic accessory spleen exhibiting abrupt changes in serum carbohydrate antigen 19-9 level: a case report - Chisato Takagi; Nobuo Hoshi; Yutaro Kikuchi; Hirofumi Shirakawa; Moriaki Tomikawa; Iwao Ozawa; Shoichi Hishinuma; Yoshiro Ogata (Surgical Case Reports)
Abstract Background Epidermoid cyst within an intrapancreatic accessory spleen (ECIAS) is a rare disease. While the detection of solid components relevant to an accessory spleen is a key diagnostic finding, the differential diagnosis between ECIAS and malignant tumors is difficult without resection in patients with no other findings of an accessory spleen. Case presentation A 73-year-old male was found to have an elevated carbohydrate antigen (CA) 19-9 level (95 U/mL) at an annual checkup, and a cystic lesion in the pancreatic tail was located by abdominal ultrasound. Abdominal magnetic resonance imaging (MRI) revealed a multicystic mass, 24 mm in diameter, which exhibited varying intensities on T2-weighted images. There were no findings suggesting solid components on contrast-enhanced computed tomography and magnetic resonance imaging. Re-evaluation of serum CA 19-9 level revealed a rapid increase to 901 U/mL, which declined to 213 U/mL 3 weeks later. Ruling out the lesion’s malignant potential was difficult, and the patient underwent distal pancreatectomy with splenectomy. Histological findings revealed an ECIAS including multiple cysts, with the mucinous component of each cyst exhibiting different stages of biological reaction; one ruptured cyst exhibited inflammatory changes. Conclusions Careful observation for changes in serum CA 19-9 level and MRI findings might facilitate the diagnosis of ECIAS without a solid component by imaging studies.